AN EMPIRICAL STUDY ON THE APPLICATION OF DESIGN THINKING IN CONSULTING IN INFORMATION TECHNOLOGY INDUSTRY IN INDIA - Kancharla, Mohan (Digital Repository of Theses, 2023)
Traditionally, the word ‘Design’ is used to describe the visual aesthetics of objects. However, the meaning of this word has evolved and it is not that limited anymore. In the context of business, design is not just about form or physical attributes; it is about a new method of thinking about products and services. ‘Design Thinking’ uses creative and innovative techniques to put customer needs at the heart of development strategy. Design thinking in products is widely prevalent, design thinking in services is evolving. Though there have been many studies on application of design thinking in product development, and to some extent improving efficiency in services, there has not been much research focused on ‘Design thinking in Consulting’. The purpose of the current study is to provide a comprehensive review of design thinking as applied to business and outline a conceptual framework for applying the principles and practices of design thinking to consulting in the information technology industry in India. Design thinking Principles are the fundamental ideas or general rules that are true regardless of the circumstances, they are the propositions that serve as the foundation for design thinking (e.g., Human centered design). Design thinking Practices on the other hand are the tools or techniques by which the expected outcomes of the principles are achieved (e.g., Empathy maps). The matrix of the such principles applicable for consulting in its entirety along with associated practices, is the ‘Design Grid’, the proposed conceptual framework for this research. The study covers information technology organizations in India, providing consulting services. Research method used was mixed methods methodology; online surveys with a larger set of consulting practitioners to address generality and focus group discussions with a smaller set of experts on specific consulting types plus qualitative semi-structured interviews with limited industry leaders to address particularity. The outcome of this study will be relevant to both the organizations and practitioners in the IT industry. Results from survey were tabulated on five themes - consulting capability, design thinking awareness, design thinking principles, design thinking practices and design thinking in consulting. The first four themes are results from the survey. The fifth theme is results from focus group discussions. Findings revealed a very strong consulting capability and a high level of awareness of design thinking amongst respondents. In the focus group discussions - all five design thinking principles and twelve design thinking practices of the Design grid found applicability in all the consulting phases across all consulting types, demonstrating the breadth and depth of usage of design thinking principles and practices. Leaders from the Indian IT industry acknowledged survey findings and advocated that the conceptual framework (i.e.) the ‘Design grid’ can be a force-multiplier for applying Design thinking in Consulting.